Turn‐on Circularly Polarized Luminescence in Chiral Indium Chlorides by 5s2 Metal Centers. Issue 17 (10th January 2023) - Wang, Zhiyu; Wang, Xiaoming; Chen, Zhongwei; Liu, Yang; Xie, Huilin; Xue, Jie; Mao, Lingling; Yan, Yanfa; Lu, Haipeng
Abstract: Introducing chirality into the metal‐halide hybrids has enabled many emerging properties including chiroptical activity, spin‐dependent transport, and ferroelectricity. However, most of the chiral metal‐halide hybrids to date are non‐emissive, and the underlying mechanism remains elusive. Here, we show a new strategy to turn on the circularly polarized luminescence (CPL) in chiral metal‐halide hybrids. We demonstrate that alloying Sb 3+ into chiral indium‐chloride hybrids dramatically increases the photoluminescence quantum yield in two new series of chiral indium‐antimony chlorides. These materials exhibit strong CPL signals with tunable energy and a high dissymmetry factor up to 1.5×10 −2 . Mechanistic studies reveal that the emission originates from the self‐trapped excitons centered in 5s 2 Sb 3+ . Moreover, near‐ultraviolet pumped white light is demonstrated with a polarization up to 6.0 %. Our work demonstrates new strategies towards highly luminescent chiral metal‐halide hybrids. Abstract : This study reports two new series of chiral indium‐antimony chlorides, ( R ‐MPA)4 In2(1− x ) Sb2 x Cl10 and ( R ‐CHEA)4 In2(1− x ) Sb2 x Cl10 (( R )‐(+)‐β‐methylphenethylamine ( R ‐MPA), ( R )‐(−)‐1‐cyclohexylethylammonium ( R ‐CHEA)) with tunable PLQY and luminescence dissymmetry factors. The bright STE emission is generated from lone pair 5s 2 electrons of Sb 3+ . Near‐ultraviolet pumped white light is demonstrated with a circular polarization up to 6.0 %.